PENINGKATAN KETERAMPILAN MENDENGARKAN CERITA ANAK MELALUI MEDIA AUDIO VISUAL PADA SISWA KELAS I SDN 020 KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Darna Darna (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low listening skill of class I students of SDN 020 Kualu Nenas KecamatanTambang Kabupaten Kampar. The purpose of this study is to improve children's listening skills through audiovisual media. This research was conducted at SDN 020 Kualu Nenas Kecamatan Tambang Kabupaten Kampar.The subjects of this study are the students of class I with the number of 28 people. This classroom actionresearch began to take place in early August 2016. This form of research is a classroom action research. Theinstrument of this research consisted of instrument of activity sheet of teacher and student and test of storylistening skill. Based on the results of research and data analysis can be concluded that the use of audio-visualmedia can improve the listening skills of children's stories students class I SDN 020 Kualu Nenas KecamatanTambang Kabupaten Kampar. This success is known from the average student skill score at the second meetingof the second cycle. Where in the initial data only obtained average value 66.8, at the meeting 1 cycle I obtainedan average of 72.3, at meeting 2 cycle I obtained an average of 73.8, at meeting 1 cycle II obtained an averageof 77, 1, at the second meeting of cycle II obtained an average of 83.6, while the completeness obtained by allstudents. This indicates that the audio-visual media can improve the listening skills of children's story grade ISDN 020 Kualu Nenas Kecamatan Tambang Kabupaten Kampar.